Mixed reality for extraction of maxillary mesiodens - Yu Koyama; Keisuke Sugahara; Masahide Koyachi; Kotaro Tachizawa; Akira Iwasaki; Ichiro Wakita; Akihiro Nishiyama; Satoru Matsunaga; Akira Katakura (SpringerOpen, 2023)
Abstract Background Mesiodentes are the most common supernumerary teeth. The cause is not fully understood, although proliferations of genetic factors and the dental lamina have been implicated. Mesiodentes can cause delayed or ectopic eruption of permanent incisors, which can further alter occlusion and appearance. Careful attention should be paid to the position and direction of the mesiodentes because of possible damage to adjacent roots in the permanent dentition period, errant extraction in the deciduous and mixed dentition periods, and damage to the permanent tooth embryo. To avoid these complications, we applied mixed reality (MR) technology using the HoloLens® (Microsoft, California). In this study, we report on three cases of mesiodentes extraction under general anesthesia using MR technology. Results The patients ranged in age from 6 to 11 years, all three were boys, and the direction of eruption was inverted in all cases. The extraction approach was palatal in two cases and labial in one case. The average operative time was 32 min, and bleeding was minimal in all cases. No intraoperative or postoperative complications occurred. An image was shared preoperatively with all the surgeons using an actual situation model. Three surgeons used Microsoft HoloLens® during surgery, shared MR, and operated while superimposing the application image in the surgical field. Conclusions The procedure was performed safely; further development of MR surgery support systems in the future is suggested.